Stoichiometric coupling of brain glucose metabolism and glutamatergic neuronal activity - Sibson, Nicola R. (National Academy of Sciences, 1998)
To determine the relationship between cerebral Glc metabolism and glutamatergic neuronal function, we used (13)C NMR spectroscopy to measure, simultaneously, the rates of the tricarboxylic acid cycle and Gln synthesis in the rat cortex in vivo. From these measurements, we calculated the rates of oxidative Glc metabolism and glutamate–neurotransmitter cycling between neurons and astrocytes (a quantitative measure of glutamatergic neuronal activity). By measuring the rates of the tricarboxylic acid cycle and Gln synthesis over a range of synaptic activity, we have determined the stoichiometry between oxidative Glc metabolism and glutamate–neurotransmitter cycling in the cortex to be close to 1:1. This finding indicates that the majority of cortical energy production supports functional (synaptic) glutamatergic neuronal activity. Another implication of this result is that brain activation studies, which map cortical oxidative Glc metabolism, provide a quantitative measure of synaptic glutamate release.